Islamic Judiciary and Disposition of Testimonial Evidence (Urdu) - Dr. Aasia Rashid (Journal of Islamic and Religious Studies, 2017)
The establishment and implementation of justice is the primary responsibility of the Islamic state. In every Islamic society, the establishment of the systems of justice and police become an obligation and a necessity for the betterment of society and for the solution of the problems faced. The present research deals with the issue of Islamic system of judiciary highlighting its various components in the light of Shari‘ah. Oath, Evidence, Witness and various technical terms used in the dissemination of Ajustice are explained with evidences from Qur’┐n and Sunnah of the Holy Prophet (S.A.W). So this research concludes with the note that if the system of justice be strengthened; all the problems, in particular elimination of crimes can take place, and decisions can be given in the light of the laws and orders in the light of the Shari‘ah.